Anti-inflammatory effect of naringin and sericin combination on human peripheral blood mononuclear cells (hPBMCs) from patient with psoriasis - Raksawan Deenonpoe; Pokpong Prayong; Nattakarn Thippamom; Jitlada Meephansan; Kesara Na-Bangchang (BMC, 2019)
Abstract Background Several immunological pathways, particularly skin inflammation via various pro-inflammatory cytokines have been reported to be involved in the pathogenesis and clinical manifestations of psoriasis. The aim of the study was to investigate the potential role of naringin from Citrus maxima (Burm.) Merr and sericin from Bombyx mori combination in the treatment of psoriasis. Inhibitory effects on the expression of mRNA and the production of pro-inflammatory cytokines (TNF-α, IL-6, IL-23, and IL-12p40) were investigated. Methods Human peripheral blood mononuclear cells (hPBMCs) were isolated from 10 healthy subjects and 10 patients with psoriasis. The hPBMCs from each group were exposed to naringin or sericin alone, and the combination of naringin and sericin. The expression levels of mRNA and the production of all cytokines were determined using quantitative RT-PCR and ELISA, respectively. Results Naringin/sericin combination significantly decreased the expression of mRNA and the production of all pro-inflammatory cytokines in hPBMCs from patients with psoriasis. The potency of inhibitory activity was markedly higher than naringin or sericin alone. Conclusion The activity of naringin/sericin combination on down-regulation of these pro-inflammatory cytokines suggested its potential clinical use in psoriasis as well as other inflammation-associated diseases. The combination might be used as a complementary therapy with conventional treatment in psoriasis to improve clinical efficacy and tolerability.